The interferon landscape along the respiratory tract impacts the severity of COVID-19 - Sposito, Benedetta; Broggi, Achille; Pandolfi, Laura; Crotta, Stefania; Clementi, Nicola; Ferrarese, Roberto; Sisti, Sofia; Criscuolo, Elena; Spreafico, Roberto; Long, Jaclyn M; Ambrosi, Alessandro; Liu, Enju; et al. (Cell, 2021)
Severe coronavirus disease 2019 (COVID-19) is characterized by overproduction of immune mediators, but the role of interferons (IFNs) of the type I (IFN-I) or type III (IFN-III) families remains debated. We scrutinized the production of IFNs along the respiratory tract of COVID-19 patients and found that high levels of IFN-III, and to a lesser extent IFN-I, characterize the upper airways of patients with high viral burden but reduced disease risk or severity. Production of specific IFN-III, but not IFN-I, members denotes patients with a mild pathology and efficiently drives the transcription of genes that protect against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In contrast, compared to subjects with other infectious or noninfectious lung pathologies, IFNs are overrepresented in the lower airways of patients with severe COVID-19 that exhibit gene pathways associated with increased apoptosis and decreased proliferation. Our data demonstrate a dynamic production of IFNs in SARS-CoV-2-infected patients and show IFNs play opposing roles at distinct anatomical sites.